2018
DOI: 10.3389/fpls.2018.01104
|View full text |Cite
|
Sign up to set email alerts
|

Developing New Oligo Probes to Distinguish Specific Chromosomal Segments and the A, B, D Genomes of Wheat (Triticum aestivum L.) Using ND-FISH

Abstract: Non-denaturing FISH (ND-FISH) technology has been widely used to study the chromosomes of Triticeae species because of its convenience. The oligo probes for ND-FISH analysis of wheat (Triticum aestivum L.) chromosomes are still limited. In this study, the whole genome shotgun assembly sequences (IWGSC WGA v0.4) and the first version of the reference sequences (IWGSC RefSeq v1.0) of Chinese Spring (T. aestivum L.) were used to find new tandem repeats. One hundred and twenty oligo probes were designed according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 55 publications
(121 reference statements)
0
65
0
Order By: Relevance
“…However, these mini-satellite arrays in wheat represented moderately repeated families of less than 100 copies per array. Tang et al [47] reported five probes with mini-satellite sequences among ND-FISH probes as predicted by TRF, and we predicted 120 to 260 copy numbers across specific chromosome regions with total lengths of under 20 kb by B2DSC web server. The present study found that Ta-3A1 represented the highest copy number of a mini-satellite yet reported, and it covered a total length of over 2 Mb and was mainly located on five chromosomes of wheat (Figure 1).…”
Section: Discussionmentioning
confidence: 66%
“…However, these mini-satellite arrays in wheat represented moderately repeated families of less than 100 copies per array. Tang et al [47] reported five probes with mini-satellite sequences among ND-FISH probes as predicted by TRF, and we predicted 120 to 260 copy numbers across specific chromosome regions with total lengths of under 20 kb by B2DSC web server. The present study found that Ta-3A1 represented the highest copy number of a mini-satellite yet reported, and it covered a total length of over 2 Mb and was mainly located on five chromosomes of wheat (Figure 1).…”
Section: Discussionmentioning
confidence: 66%
“…The ND-FISH based chromosome painting technique with the labelled oligonucleotide (oligo) is widely applied, due to obvious advantages over conventional FISH procedures, such as easy probes synthesis, flexible design, relatively low cost, and high-throughput [25,30,[36][37][38][39]. This technique has been successfully used for distinguishing different genomes, such as Oligo-1162 for Secale cereale [30] and Oligo-B and Oligo-D for wheat B-and D-chromosomes [39], respectively. GISH by using D. villosum genomic DNA as a probe [13,15], and FISH using Dasypyrum specific LTR pDb12H probe can distinguish the J S chromosomes of Th.…”
Section: Discussionmentioning
confidence: 99%
“…Such probes, designed from conserved sequences of one species were used e.g. for developing karyotype among genetically related Solanum species , for differentiating of A, B, and D genomes in wheat (Tang et al, 2018), in comparative physical mapping of sex chromosomes in Populus (Xin et al, 2018) and in examination of meiotic pairing in polyploid Solanum species .…”
Section: Introductionmentioning
confidence: 99%